2024
DOI: 10.2196/49780
|View full text |Cite
|
Sign up to set email alerts
|

Race and Socioeconomic Status as Predictors of Willingness to Use Digital Mental Health Interventions or One-On-One Psychotherapy: National Survey Study

Lorenzo Lorenzo-Luaces,
Akash Wasil,
Corinne N Kacmarek
et al.

Abstract: Background There is an ongoing debate about whether digital mental health interventions (DMHIs) can reduce racial and socioeconomic inequities in access to mental health care. A key factor in this debate involves the extent to which racial and ethnic minoritized individuals and socioeconomically disadvantaged individuals are willing to use, and pay for, DMHIs. Objective This study examined racial and ethnic as well as socioeconomic differences in partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The most highly represented sociodemographic subgroups among meditation users in 2022 were younger-to-middle-aged (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), female, White or 'Other' race, not in a relationship, more educated (bachelor, master or higher), and residing in the West (Figure 1, Table 1, Table S6). The least represented groups were young (18)(19)(20)(21)(22)(23)(24) or older (45-64, 65+), male, Hispanic race, in a relationship, less educated (less than high school, high school) and residing in the South.…”
Section: Meditationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most highly represented sociodemographic subgroups among meditation users in 2022 were younger-to-middle-aged (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44), female, White or 'Other' race, not in a relationship, more educated (bachelor, master or higher), and residing in the West (Figure 1, Table 1, Table S6). The least represented groups were young (18)(19)(20)(21)(22)(23)(24) or older (45-64, 65+), male, Hispanic race, in a relationship, less educated (less than high school, high school) and residing in the South.…”
Section: Meditationmentioning
confidence: 99%
“…Studies of meditation have highlighted potential harms that include prolonged adverse experiences among approximately 10% of users [41][42][43] . A recent cross-sectional survey found that low income and self-guided training via apps may be associated with adverse experiences, with first exposure via apps potentially associated with lasting impairment 42 (noting that lower socioeconomic groups are also more likely to try digital mental health 44 , and also experience more acute distress and greater mental health need which itself predicts adverse experiences 43,45 ). To plan appropriate public health services that maximize benefits and minimize harms, it is essential to know who is using CAM practices to understand whether they are safe, and suited to meet the needs for which they are being used.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of meditation have highlighted potential harms that include prolonged adverse experiences among approximately 10% of users 41 – 43 . A recent cross-sectional survey found that low income and self-guided training via apps may be associated with adverse experiences, with first exposure via apps potentially associated with lasting impairment 42 (noting that lower socioeconomic groups are also more likely to try digital mental health 44 , and also experience more acute distress and greater mental health need which itself predicts adverse experiences 43 , 45 ). To plan appropriate public health services that maximize benefits and minimize harms, it is essential to know who is using CAM practices to understand whether they are safe, and suited to meet the needs for which they are being used.…”
Section: Introductionmentioning
confidence: 99%